Diseño de un sistema de aire acondicionado para confort térmico, aire acondicionado de precisión y ventilación industrial para los edificios de administración, laboratorio de control de calidad y laboratorio de metrología de RECOPE, Plantel El Alto, Ochomogo, acorde a la norma ASHRAE - Cascante-Gómez, Rafael Ángel (Instituto Tecnológico de Costa Rica, 2018)
The development of this professional practice report consists in the design of three different air control system. Thermal comfort air conditioning, precision air conditioning and industrial ventilation are going to be applied as a solution to the requirement of three buildings. Metrology laboratory, quality control laboratory and two level of administration building are located in Ochomogo, Cartago. Since each one has different design considerations; the solution is developed for each air control. The air conditioning design for thermal comfort conditions are 23°C and 50% of relative humidity (%RH) in all the rooms to intervene. The equipment will have to be able to adapt cooling load and guarantee that the set conditions are going to endure no matter how the load changes along the time the equipment is used. The second system precision air conditioning, as the name suggests, must be able to keep both of the set conditions of 20°C and 50% RH within an exactness range define by the client. Therefore, the equipment has to handle the temperature as well as the relative humidity to secure the set conditions to stay in the definite range. The design has to provide the proper distribution of the air to guarantee the precision in the rooms to intervene. The ventilation system has to provide the air change rate according to each room. Also, must consider the air distribution and the selection of the equipment’s. After the complete design is done, to finish the report it is necessary to make an initial budget for execution of the project and the recommendations to improve it.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Ventilación; Aire; Confort; Precisión; Control